2018
DOI: 10.21037/tau.2018.03.20
|View full text |Cite
|
Sign up to set email alerts
|

Percent Gleason pattern 4 in stratifying the prognosis of patients with intermediate-risk prostate cancer

Abstract: The Gleason score remains the most reliable prognosticator in men with prostate cancer. One of the recent important modifications in the Gleason grading system recommended from the International Society of Urological Pathology consensus conference is recording the percentage of Gleason pattern 4 in the pathology reports of prostate needle biopsy and radical prostatectomy cases with Gleason score 7 prostatic adenocarcinoma. Limited data have indeed suggested that the percent Gleason pattern 4 contributes to str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…As the percentage of Gleason pattern 4 is currently being reported in the diagnosis, a number of research studies have been carried out to establish a category of patients with a ‘favourable’ prognosis who would benefit from AS. So far, these studies have found that patients with ‘favourable’ Gleason 3 + 4 = 7 (GrG2) still have a higher risk of Gleason grade 4 + 3 = 7 (GrG), EPE, and seminal vesicle invasion at RP, and a higher risk of BCR, than low‐risk men undergoing RP .…”
Section: Significant Prostate Cancer At Rpmentioning
confidence: 99%
See 2 more Smart Citations
“…As the percentage of Gleason pattern 4 is currently being reported in the diagnosis, a number of research studies have been carried out to establish a category of patients with a ‘favourable’ prognosis who would benefit from AS. So far, these studies have found that patients with ‘favourable’ Gleason 3 + 4 = 7 (GrG2) still have a higher risk of Gleason grade 4 + 3 = 7 (GrG), EPE, and seminal vesicle invasion at RP, and a higher risk of BCR, than low‐risk men undergoing RP .…”
Section: Significant Prostate Cancer At Rpmentioning
confidence: 99%
“…On analysis of RP specimens of patients that would have met the criteria for AS except for a minor component of Gleason pattern 4 at needle biopsy, the rate of adverse findings was significantly higher in this group (21.6%) than in controls, the most common being Gleason grade 4 + 3 = 7 or higher (GrG ≥ 3). 35 As the percentage of Gleason pattern 4 is currently being reported in the diagnosis, 32,36,37 a number of research studies have been carried out to establish a category of patients with a 'favourable' prognosis who would benefit from AS. So far, these studies have found that patients with 'favourable' Gleason 3 + 4 = 7 (GrG2) still have a higher risk of Gleason grade 4 + 3 = 7 (GrG), EPE, and seminal vesicle invasion at RP, and a higher risk of BCR, than low-risk men undergoing RP.…”
Section: T U M O U R G R a D E I N S I G N I F I C A N T C A N C E R mentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the visual estimation of %G4 differed from the digital one; accurate measurement of the G4 burden has been shown to help risk-stratify patients 9 , 17 . In a study by de Souza et al .…”
Section: Discussionmentioning
confidence: 75%
“…Despite these differences, the Bland-Altman analysis showed good concordance between the two measurements; thus, the accuracy of the MCCL is not compromised when a digital tool is used. In our study, the visual estimation of %G4 differed from the digital one; accurate measurement of the G4 burden has been shown to help risk-stratify patients 9,17 . In a study by de Souza et al, 20% of Gleason 3 + 4 tumours had more extensive G4 disease than the first quartile of 4 + tumours in radical prostatectomy specimens 18 .…”
Section: Discussionmentioning
confidence: 75%